Eficácia do glyphosate e 2,4-d no controle de commelina villosa - Campos, Caio Ferraz de [UNESP]; Rodrigues, Andreia C. P.; Cardoso, Leonildo Alves [UNESP]; Pereira, Maria Renata Rocha [UNESP]; Souza, Guilherme Sasso Ferreira de [UNESP]; Martins, Dagoberto [UNESP] (My University, 2013)
The aim of this study was to evaluate the efficacy of glyphosate and 2,4-D alone and in combination, in the control of Commelina villosa. We studied two methodologies for evaluating herbicide absorption in eight time intervals for washing (simulating rainfall after application) and cutting of leaves (simulating abortion as a defense strategy): 2, 4, 6, 8, 12, 24 and 48 hours after herbicide application, and a treatment without washing or cutting the leaves in a completely randomized design with four replications in a 3 x 7 + 1 factorial design (three herbicides x seven periods – hours after application). Herbicides and doses tested were: glyphosate (1,440 g ha-1), 2,4-D (720 g ha-1) and a mixture of glyphosate + 2,4-D (1,080 + 720 g ha-1). The simulation of rain interfered negatively in the plant control with glyphosate. The control with the herbicide 2,4-D was affected only for the period of 2 hours. Periods of rain simulation did not influence the control of plants with a mixture of glyphosate + 2,4-D. For the study with the cutting of treated leaves, all treatments regardless of the period of cutting the leaves were influenced negatively in terms of plant control, the plants showing regrowth when treated with 2,4-D alone.

O objetivo do presente trabalho foi avaliar a eficácia de glyphosate e 2,4-D, isolados e em mistura, no controle de Commelina villosa. Foram estudadas duas metodologias de avaliação de absorção de herbicidas em oito intervalos de tempo para a lavagem (simulando chuva após a aplicação) e corte (simulando abortamento, como estratégia de defesa) das folhas: 2, 4, 6, 8, 12, 24 e 48 horas após a aplicação dos herbicidas, além de um tratamento sem lavagem ou corte das folhas, em delineamento experimental inteiramente casualizado com quatro repetições, dispostos em um esquema fatorial 3 x 7 + 1 (três herbicidas x sete períodos – horas após a aplicação). Os herbicidas e doses testados foram: glyphosate (1.440 g ha-1), 2,4-D (720 g ha-1) e a mistura glyphosate + 2,4-D (1.080 + 720 g ha-1). A simulação de chuva interferiu de forma negativa no controle das plantas com o herbicida glyphosate. O controle com o herbicida 2,4-D foi influenciado apenas no período de 2 horas. Os períodos de simulação de chuva não influenciaram no controle das plantas com a mistura de glyphosate + 2,4-D. Para o estudo com corte das folhas tratadas, todos os tratamentos independente do período para corte das folhas foram influenciados de forma negativa no controle, sendo que as plantas apresentaram rebrotas quando tratadas com o herbicida 2,4-D isolado.
Efficacy of glyphosate and 2,4-d in the control of commelina villosa
Keywords: Dayflower; Commelinaceae; Herbicide; Trapoeraba; Commelinaceae; Herbicida